Prevalence of gestacional depression and associated factors (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Depression is a common mental disorder during pregnancy and is associated with several risk factors. Studies have reported an association between gestational depression and deleterious effects to the development of the infant. OBJECTIVES: To review the prevalence and risk factors for depression during pregnancy. METHODS: The keywords: "depression during pregnancy" OR "gestational depression" OR "antenatal depression" AND "prevalence" AND "risk factors" were used to search for articles published between 1997 and 2007 in the Medline, Lilacs and Scielo databases. RESULTS: The prevalence of depression during pregnancy in developing countries, including Brazil, was higher than in developed countries, respectively 20% and 15%. Despite being an important public health issue, there are few studies about this subject in Brazil. The main risk factors were: previous history of depression, financial difficulties, low level of education, unemployment, poor social support, substance dependence and domestic violence. DISCUSSION: We emphasize the importance of the screening for depression in the context of antenatal care. Obstetricians and other related health care providers must be aware of the various risks factors for depression during pregnancy. In addition, psychosocial interventions and social policies need to be implemented in this population.